Better Together and the No Campaign: from Project Fear to Grace? - Fiona Simpkins (Revue Française de Civilisation Britannique, 2015)
Better Together was the main umbrella organisation of the No camp during the 2014 Scottish independence referendum campaign. It represented the common effort of three otherwise unlikely-minded British parties to work together and publicly collaborate to safeguard the Union. The difficulties that this collaboration represents were immense in that the three participating parties had distinct electoral and political histories in Scotland and each faced inner divisions and distinct challenges which this paper seeks to examine.